RRNS Based Multiple Error Detection and Correction in CDMA System - Jasmin, M.; Philomina, S.; Virgin, G. Angelo (International Journal of Psychosocial Rehabilitation, 2018)
In communication systems corruption of data and hacking of data is unavoidable. These are the major problems we are facing in communication system. This project presents an enhanced multiple error detection and correction scheme based on the Redundant Residue Number System (RRNS). RRNS is often used in parallel processing environments because of its ability to increase the robustness of information passing between the processors. The proposed multiple error correction scheme utilizes the Chinese Remainder Theorem (CRT) together with a novel algorithm that significantly simplifies the error correcting process for integers. This enhanced scheme is compared with the existing method and this enhanced scheme is used in the CDMA application.